Are Natural Resources Important Elements in The National Tourism Policy? Examples of European Countries - MARCZAK, Mirosław; BORZYSZKOWSKI, Jacek (Journal of Environmental Management and Tourism, 2020)
Natural resources constitute an important element of tourism assets and they considerably determine the shape and the level of tourist destination attractiveness. The present article constitutes an attempt made to estimate the significance of such elements in activities undertaken within the framework of tourism policy accepted by particular European countries. Two main research methods are used in the article, namely: a) desk research: based on information collected from reports submitted by particular countries to the European Commission; b) original research with the use of a diagnostic survey method (carried out with a group of 39 European national tourism organisations). As indicated in the article, natural resources constitute a very important element in activities undertaken to create and to develop tourism in the countries analysed. The individual countries certainly appreciate the value of the above-mentioned factors, especially in the context of proper care which needs to be provided to ensure an appropriate use by tourists. The results obtained need to become an important reference point for those decision-makers who are responsible for the development of tourism. They also emphasize the on-going necessity of undertaking activities aim at the protection of natural resources, as viewed from the perspective of the growing interest in tourism.